Solving the puzzle of Li4Ti5O12 surface reactivity in aprotic electrolytes in Li-ion batteries by nanoscale XPEEM spectromicroscopy. Issue 8 (5th February 2018) - Leanza, Daniela; Vaz, Carlos A. F.; Czekaj, Izabela; Novák, Petr; El Kazzi, Mario
Abstract : Preferential reduction of solvents solely on LTO particles, caused by their adsorption at the outer surface planes during lithiation. Abstract : The safe operation and long life-span of Li-ion batteries rely on a stable electrode–electrolyte interface. However, determining the thermodynamic stability window of such an interface is challenging due to the different (electro)chemical reactivities of the electrode components. Here we demonstrate a holistic experimental and theoretical approach to elucidate the nature and origin of the multiple reactions at such complex interfaces, which remain a major obstacle for the development of next generation Li-ion batteries. We applied X-ray photoemission electron microscopy (XPEEM) on Li4 Ti5 O12 electrodes to solve, with nanoscale resolution, its controversial surface reactivity in carbonate-based electrolytes. Local X-ray absorption spectroscopy (XAS) is performed upon cycling on individual carbon and Li4 Ti5 O12 particles, while maintaining their working environment, as in the commercial-like electrode composition. Despite the theoretical prediction of a stable electrochemical interface, we find that electrolyte reduction occurs solely on Li4 Ti5 O12 particles during lithiation at 1.55 V vs. Li + /Li. With the support of density functional theory (DFT) calculations, we show that this behavior is caused by the solvents adsorbed on the Li4 Ti5 O12 outer planes driven by the Li-ion insertion. The DFT results indicate that Li-ion insertion leads to a shift of the LUMO of the adsorbed solvents to energies below the Fermi level position of lithiated Li7 Ti5 O12 and thus to chemical instability. Simultaneously, at the same potential, we detect a competing reaction that leads to the partial dissolution of the electrolyte by-product layer. Such a finding has to be considered for other insertion materials and needs to be addressed in surface engineering to mitigate side reactions and design safe and long-lasting batteries.